Modification of Method for Drusen Detection in Eye Fundus Images - Patašius, M.; Marozas, V.; Jegelevičius, D.; Lukoševičius, A.; Špečkauskas, M. (Elektronika ir Elektrotechnika, 2010)
Drusen are white or yellow spots in eye fundus that consist of extracellular material. They are a sign of age-related macular degeneration (AMD) – the main cause of blindness in the developed countries and a third main cause of blindness in the whole world. Previously a drusen detection method based on optimized colour combinations has been proposed, but it has only been investigated empirically. Thus here this method is investigated using one-dimensional and two-dimensional models of drusen, its properties are found and improvements suggested.